Independent perioperative predictive risk factors for the anastomotic leak after emergency bowel resection anastomosis - Sieda, Bassem; Abdelhady, Waleed; Baghdadi, Muhammad (International Surgery Journal, 2019)
Background: Anastomotic disruption after bowel resection anastomosis is a devastating and a feared complication, so it is of utmost importance to identify perioperative parameters predisposing to such complication. Methods: A prospective cohort study was performed in two institutes, and there were 287 patients eligible and included in the study which done from April 2017 to December 2018, 87 patients underwent intervention in the first institute in Zagazig University Hospitals, Egypt. And 200 patients underwent intervention in Riyadh, KSA. Statistical analysis used: Percent of categorical variables were compared using Pearson’s Chi-square test or Fisher's exact test when was appropriate. Risk estimation was done by Odds ratio (OR) calculation. All tests were two sided. A p-value <0.05 was considered significant. All statistics were performed using SPSS 22.0 for Windows (SPSS Inc., Chicago, IL, USA) and MedCalc windows (MedCalc Software bvba 13, Ostend, Belgium). Results: Of the parameters analyzed risk factors for anastomotic leakage that studied in 287 patients, 6 perioperative parameters have significant statistical difference: hypo-albuminaemia (Odd ratio: 6.544 and p-value <0.001), acute intra-abdominal contamination (Odd ratio: 3.921 and P-value <0.004), High WBC'S with high presepsin with p-value <0.001, hyponatremia p<0.004, perioperative blood transfusion and anastomotic tension were found to be independent factors. Conclusions: Knowledge of independent perioperative predictive factors for leakage is of utmost importance for its early detection, decision making for surgical time,our study concluded the possibility to detect a subgroup of high-risk patients for anastomotic leakage after emergency bowel resection anastomosis.